Against an ideological criminal process (Revista do Tribunal Regional Federal da 3ª Região, 2013)
In this article, it’s studied the necessity to avoid the contamination of the criminal procedure by ideological biases. Three themes are detached: ideological bias against policemen, prosecutors and judges; enemy criminal law; and the ideology of overcoming impunity in the international criminal procedure.
Keywords: ideology; bias; criminal procedure